How do different network positions affect crowd members' success in crowdsourcing challenges?. Issue 3 (20th March 2023) - Mazzola, Erica; Piazza, Mariangela; Perrone, Giovanni
Abstract: In the crowdsourcing challenges, crowd members can interact with each other by, for example, chatting, exchanging feedback, providing advice, discussing, and commenting on ideas. These social interactions shape a network structure, which is a set of social relationships developed by crowd members. This study aims at investigating how occupying diverse network positions within a crowdsourcing challenge network increases the members' likelihood to succeed in a competition. Leveraging prior literature on social networks and crowdsourcing research, we theorize how central and structural hole network positions influence the crowd members' likelihood of winning crowdsourcing challenges by leveraging the knowledge and information flows that they can access through such network positions. To empirically test the developed hypotheses, we built a crowdsourcing challenge network shaped by 2479 members registered in the 99designs crowdsourcing platform. We found that both occupying a central position and assuming a structural hole network position within the crowdsourcing challenge network showed an inverted U‐shaped effect on the success of crowd members. The results of this study contribute to previous crowdsourcing literature and provide critical implications for crowd members and managers organizing crowdsourcing competitions.